2017
DOI: 10.1021/acsnano.7b01350
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous, Three-Dimensional Wood Membrane Decorated with Nanoparticles for Highly Efficient Water Treatment

Abstract: Wood, an earth-abundant material, is widely used in our everyday life. With its mesoporous structure, natural wood is comprised of numerous long, partially aligned channels (lumens) as well as nanochannels that stretch along its growth direction. This wood mesostructure is suitable for a range of emerging applications, especially as a membrane/separation material. Here, we report a mesoporous, three-dimensional (3D) wood membrane decorated with palladium nanoparticles (Pd NPs/wood membrane) for efficient waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
258
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(264 citation statements)
references
References 51 publications
4
258
0
2
Order By: Relevance
“…This sophisticated structure has important effects on wood properties, especially related to moisture control, strength‐to‐weight ratio, and anisotropy. Moreover, recent studies have shown that wood's structural features are useful for a wide range of potential applications, such as mechanically stable scaffolds for stimuli‐responsive hydrogels, natural templates for nanoparticle assembly, wood membranes for water treatment, and water extraction . However, its hierarchical structure is underused in most wood‐based materials and, therefore, its beneficial properties cannot be fully leveraged …”
Section: Introductionmentioning
confidence: 99%
“…This sophisticated structure has important effects on wood properties, especially related to moisture control, strength‐to‐weight ratio, and anisotropy. Moreover, recent studies have shown that wood's structural features are useful for a wide range of potential applications, such as mechanically stable scaffolds for stimuli‐responsive hydrogels, natural templates for nanoparticle assembly, wood membranes for water treatment, and water extraction . However, its hierarchical structure is underused in most wood‐based materials and, therefore, its beneficial properties cannot be fully leveraged …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Sustainable materials become ap riority on the list of world interests as part of the solution to replacet he non-renewable materials to moderate the environmental impact. [7][8][9][10] To address the issue of energy shortage, it is highly desired to reduce the energy consumption of residential and commercial buildings, because they account for over 50 %o ft he total energy consumption. However,t he intrinsic properties of wood, including low corrosion resistance, poor mechanical performance, flammability,n on-transparency, and non-thermal conductivity,have limited its applicationsinthe building indus-try.…”
Section: Introductionmentioning
confidence: 99%
“…The ever-increasing depletion of fossil fuels has caused severe environmental pollution and other relevant issues, thus the growing demand for clean and sustainable energy is very pressing [1][2][3][4]. It is noted that, the indirect energy sources such as wind energy, solar energy and tidal energy are very promising to meet the requirements of people's daily life, but they are different greatly in geography and even change over time.…”
Section: Introductionmentioning
confidence: 99%